Non-linear methods based on ultrasonic waves to analyse disbonds in single lap joints. (August 2017) - Scarselli, G; Ciampa, F; Nicassio, F; Meo, M
Adhesive bonded lap joints are widely used in the aerospace field and non-destructive testing (NDT) techniques are critical in evaluating the quality of adhesion before and during use. Two types of bonded samples have been experimentally investigated in order to verify the reliability of non-linear elastic wave spectroscopy (NEWS) based on the use of ultrasound. Piezoelectric sensors have been attached to the samples and used as generators and receivers. Both the samples have shown non-linearities in their dynamic behaviour. Non-linear metrics have been applied to their structural responses over an assigned range of excitation frequencies based on higher order harmonic analysis in order to evaluate the degree of non-linearity of the samples. Possible interpretations of the experimental behaviour are provided in the paper based also on tomographic testing of the adhesive layer that showed the presence of microbubbles in the bond due to manufacturing process.